Offshoring and labor income risk: An empirical investigation - Jan Hogrefe; Yao Yao (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper analyses how increased offshoring impacts on labor income risk. It is therefore distinct from a large number of studies explaining the level effects of globalization on the labor market in that it takes a look at effects on the variability of incomes. It provides an assessment that directly connects labor income risk and offshoring trends in a panel setting at the industry level. Importantly, we distinguish between transitory and permanent shocks to individual income. Permanent income risk is defined as variance of shocks to income that do not fade out over time. Contrary to transitory short-term fluctuations, it is furthermore assumed to be uninsurable. It thus has a particular relevance for individual welfare. Our findings suggest that offshoring tends to lower permanent income risk. This effect is particularly strong for offshoring to low-income destinations. Hence, there could be potential aggregate welfare gains when domestic firms increasingly offshore production to foreign countries.
Keywords: F16; F23; E24; 330; globalization; offshoring; labor income risk; wages